STRATEGIES FOR INCREASING THE PHYSICAL FITNESS OF EMPLOYEES IN THE WORKPLACE - Radu-Tiberiu ȘERBAN; Alin Marius BACIU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2017)
Introduction. Industrialization and the development of modern societies led to an evolution of the motor behaviour of humans. Physical tasks at the workplace got easier, tools that are more modern were invented, and in some cases, it was totally taken by machinery and robots. Unfortunately, deskwork being a sedentary activity, health related issues started to concern our society. Methods. The short review of the specialized literature has been done by abstracting data from the eligible articles resulted after searching for the related keywords in scientific databases. Results. Authors offer many reasons why strategies for increasing the physical fitness of employees should be implemented at the workplaces and give examples of successful interventions like: involving employees in health related contests, offering free or partially subsidized access to sports facilities and clubs, implementing exercises into the working day or awarding the participation in companies’ health programs with incentives. Conclusion. The lack of physical exercise affect the health status of the sedentary employees and thus his productivity and cause other derived economic, social and psychological issues. In the current context, promoting physical activity strategies at the workplace is a must. These actions are beneficial for not only the employees and employers but also for physical education and sports specialists as such actions will eventually also increase the number of jobs for them.